LEARNING MODEL OF COOPERATIVE LEARNING TYPE TEAM GAMES TOURNAMENT BASED ON E-LEARNING IN SMK NUSAJAYA TANGERANG - Ajay Supriadi; Fifit Alfiah; Mochamad Fiqri Nur Fauzan (Jurnal Techno Nusa Mandiri, 2019)
This research is motivated by gaps in teaching and learning at Nusajaya Vocational School, Tangerang. This study aims to make Cooperative Learning Type Team Learning Games based on E-learning that can increase student interest and learning attitudes at Nusajaya Tangerang Vocational School. The results of this study are e-learning that can attract students' interests and attitudes to learning. In e-learning not only contains learning material content but there is a menu for interaction with students and an interesting menu for students, then this research is a Research and Development (R & D) research on the application quality testing process using Black box testing. So that the testing of this system shows results that are very feasible to use, after being used in two-stage learning, namely cycle 1 is 68.53% and cycle 2 gets results that increase 12.94% on student interests and attitudes to 81.47%.